Ke Uji Kesegaran Ikan Tongkol (Euthynnus affinis) dan Salem Secara Organoleptik (Scomber japonicus) di Pasar Parakanmuncang: Abstrak, Pendahuluan, Bahan dan Metode, Hasil dan Pembahasan, Kesimpulan, Referensi - Junianto; Irma Nurjana; Azizah Sekar Quennanty; Adrian Rustandi; Isnaniah Alni Alfiani Permana; Muhammad Rizqi Fauzan (GEMA AGRO, 2026)
Fish is an important source of animal protein that is very popular with the Indonesian people, but its quality and freshness quickly decline after capture if not handled properly. This study aims to analyze the freshness of tuna (Euthynnus affinis) and salem (Scomber japonicus) sold in Parakanmuncang Traditional Market, Sumedang Regency, West Java, using the organoleptic test method. The assessment was conducted on five quality parameters, namely surface appearance, aroma, eyes, gills, and meat texture, with a score scale of 1-9. The results showed that salem fish had an organoleptic mean score of 7.8, indicating a very fresh condition and in accordance with consumption quality standards based on SNI 01-4110.1-2006. In contrast, tuna had an average score of only 5.4, indicating a decline in quality and non-conformity to freshness standards. The quality decline in tuna is thought to be caused by the lack of cold chain implementation during distribution and handling in the market. These findings emphasize the importance of proper post-harvest handling practices, including the application of cold temperatures, to maintain the quality and safety of consumed fish in traditional markets